2021
DOI: 10.3390/ijms22094702
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light and Dark on the Phenolic Compound Accumulation in Tartary Buckwheat Hairy Roots Overexpressing ZmLC

Abstract: Fagopyrum tataricum ‘Hokkai T10′ is a buckwheat cultivar capable of producing large amounts of phenolic compounds, including flavonoids (anthocyanins), phenolic acids, and catechin, which have antioxidant, anticancer, and anti-inflammatory properties. In the present study, we revealed that the maize transcription factor Lc increased the accumulation of phenolic compounds, including sinapic acid, 4-hydroxybenzonate, t-cinnamic acid, and rutin, in Hokkai T10 hairy roots cultured under long-photoperiod (16 h ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The actin was used as the internal control. The primers for analyzing the phenylpropanoid pathway genes expression were obtained from Park et al [ 30 ] ( Table S2 ). Each sample was evaluated in triplicate for qRT-PCR analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The actin was used as the internal control. The primers for analyzing the phenylpropanoid pathway genes expression were obtained from Park et al [ 30 ] ( Table S2 ). Each sample was evaluated in triplicate for qRT-PCR analysis.…”
Section: Methodsmentioning
confidence: 99%
“…HPLC analysis of the phenolic compounds was performed according to the protocol described by Park et al [ 30 ]. Freeze-dried root samples were pulverized into fine powder.…”
Section: Methodsmentioning
confidence: 99%
“…However, in the present study, the highest phenolic content was obtained in the R1601 infected strain followed by the R1200 and ATCC 13333 strains. Previous studies have reported that HRs have the ability to produce the highest content of metabolites due to higher growth rates; thus, HRs from several plant species have been used for the production of various phenolic compounds (Park et al, 2017a;Park et al, 2021). A similar result was obtained in these studies due to the higher growth rate of the R1601 infected strains which led to the highest accumulation of primary and secondary The key components, separating the O. basilicum hairy root induced by different Agrobacterium rhizogenes strains, are based on the VIP scores obtained through the PLS-DA model.…”
Section: Discussionmentioning
confidence: 99%
“…A. rhizogenes can cause transgenic hairy roots by transferring the T-DNA region to the host plant genome [22] and the rolA, rolB, and rolC genes in the T-DNA area are often involved in the induction of secondary metabolism in many plant species [23]. In particular, the previous studies reported that the expression of rolB and rolC is important for the activation of phosphorylation-the dephosphorylation process, which is a part of the signal transduction pathway that plays a main role in the activation of plant defense responses and elicitor recognition [24,25].…”
Section: Discussionmentioning
confidence: 99%